Literasi Media Massa Bagi Lansia di Sekolah Lansia Mappadeceng Makassar - Latief, Muh Nur; Astrid, Andi Fauziah; Syam, Ferdi (LP2M IAIN Palopo, 2024)
This study raises the issue of how older adults understand and utilize mass media in the era of new media. The research method began with observation and then interviews in the form of focus group discussions with ten elderly people from Madeceng School under the guidance of BKKBN South Sulawesi. The results of this study found a shift in the use of mass media. It turns out that the elderly no longer access newspapers and radio like in the past. Only television is still often accessed to enjoy entertainment content. At the same time, general information is mostly obtained from mass media such as news portals. The elderly use social media to find basic information. This shift confirms the new habits of the elderly, who used to spend time reading newspapers and listening to the radio at home. Keywords: Mass Media, Literacy. the Elderly